Long-Term Flow through Human Intestinal Organoids with the Gut Organoid Flow Chip (GOFlowChip) - Sidar, Barkan (Lab Chip, 2019)
Human intestinal organoids (HIOs) are millimeter-scale models of the human intestinal epithelium and hold tremendous potential for advancing fundamental and applied biomedical research. HIOs resemble the native gut in that they consist of a fluid-filled lumen surrounded by a polarized epithelium and associated mesenchyme; however, their topologically-closed, spherical shape prevents flow through the interior luminal space, making the system less physiological and leading to the buildup of cellular and metabolic waste. These factors ultimately limit experimentation inside the HIOs. Here, we present a millifluidic device called the Gut Organoid Flow Chip (GOFlowChip), which we use to “port” HIOs and establish steady-state liquid flow through the lumen for multiple days. This long-term flow is enabled by the use of laser-cut silicone gaskets, which allow liquid in the device to be slightly pressurized, suppressing bubble formation. To demonstrate the utility of the device, we establish separate luminal and extraluminal flow and use luminal flow to remove accumulated waste. This represents the first demonstration of established liquid flow through the luminal space of a gastrointestinal organoid over physiologically relevant time scales. Flow cytometry results reveal that HIO cell viability is unaffected by long-term porting and luminal flow. We expect the real-time, long-term control over luminal and extraluminal contents provided by the GOFlowChip will enable a wide variety of studies including intestinal secretion, absorption, transport, and co-culture with intestinal microorganisms.